Patterns of Inheritance Distribution in Tlogoharjo Village, Giritontro Subdistrict in the Review of Islamic Law - Maskuri, Erkham (QURU’: Journal of Family Law and Culture, 2024)
The pattern of inheritance distribution in rural communities is a complex phenomenon, especially when viewed from the perspective of Islamic law. With the diversity of ethnicities, races, languages, religions, and traditions in Indonesia, differences arise regarding the pattern of inheritance distribution in the community. The fundamental thing about the inheritance system is the distribution of inheritance that is in line with the current legal regulations. This research aims to analyze the pattern of inheritance distribution in the community of Tlogoharjo Village, Giritontro Subdistrict, with a focus on related aspects of Islamic law. This research was conducted using field research with a qualitative method with a descriptive approach which is one of the qualitative research methodologies and data collection techniques by means of observation and interviews. The results of this study are that the pattern of distribution of inheritance property both before and after the heir dies is allowed in Islamic Law as long as there is no element of harm, this is because Islamic Law accepts culture and custom as legal norms that must be obeyed if there is no deviation in it and Islamic law is flexible which can be developed according to the needs of people living in the modern era today.  Furthermore, the pattern of inheritance distribution in Tlogoharjo Village is still strongly influenced by customary values and local traditions, although Islam is formally the legal basis. However, there is a tendency for adjustments to the principles of Islamic law in the practice of inheritance distribution. For example, the inheritance rights stipulated in the Qur'an and Sunnah tend to be respected, although sometimes with interpretations adapted to the social and cultural context of the village community. This research also highlights some differences between the practice of inheritance distribution in village communities and the ideal principles of Islamic law. Factors such as lack of understanding of religious teachings, hereditary traditions and economic factors play an important role in shaping inheritance distribution patterns.